THE ROLE OF HYPOALLERGENIC FORMULA ENRICHED WITH PREBIOTIC COMPLEX IN INFANT IMMUNE RESPONSE MODULATION - T. E. Borovik; T. E. Lavrova; A. V. Surzhik; N. G. Zvonkova; S. G. Shmakova ("Paediatrician" Publishers LLC, 2012)
This review contains modern data on immunomodulation effect of breast milk feeding upon infants, on possibilities of adequate immune response formation using hypoallergenic formulas, and also evidences of efficacy of hypoallergenic formula enrichment with galactoand fructooligosaccharide prebiotic complex, confirmed by decrease in allergic and infectious morbidity.